Minister of Education and Culture Counseling Socialization No. 82 of 2015 Concerning Prevention and Management of Acts of Violence in the Education Unit Environment - Donny Setiawan; Galih Farhanto; Puji Setyaningsih; Wawan Setiawan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Lecturers have an important role in character education in higher education. In carrying out the main tasks of the Tri Dharma of Higher Education, namely conducting teaching, research and community service. Another goal of this community service is for lecturers to go directly into the community and learn about educational problems that occur in the community. Broadly speaking, this program intends to provide reinforcement to all residents in the school environment about the importance of education, especially Counseling to Permendikbud No. 82 of 2015 concerning Prevention and Management of Acts of Violence in Environmental Education Units. The function of education is to refer to a person's character or behavior and personality. Conversely, the role of education is very large in preparing and developing reliable and competitive Human Resources (HR). That is why carrying out education is a moral task that is not light. So that the importance of education in an effort to educate the nation's life, improve people's welfare, and build and build national dignity, the government is trying to pay serious attention to addressing various problems in the field of improving education starting from elementary, middle, to high levels.